Crack-healing capability and high temperature oxidation resistance of multilayer coatings for carbon-carbon composites - 윤존도; Yeonho Choi; 이홍림 (Journal of ceramic processing research, 2009)
Carbon fiber reinforced carbon matrix composites (carbon-carbon composites) are degraded very rapidly by oxidation above 400 degree C in air, and need to be protected by an oxidation resistant coating. Diverse properties are required for the coating, and the requirements can be satisfied by using a multilayer coating. We designed and fabricated a multilayer coating which had high temperature resistant refractory ceramic layers and a functional SiOC glass layer. The SiC refractory ceramic layers were prepared by CVD using silane gas as a source. The functional layer was prepared by a solution method using siloxane polymers. Oxidation tests for carbon-carbon composites coated with multilayer coating showed no weight change for the duration of 23 hours at 1500 degree C and after nine times thermal shock at a heating or cooling rate of 300-1500 K per minute. Microstructural analysis showed that the cracks were formed in the SiC layer but healed by SiOC glass. The excellent high temperature oxidation resistance was due to the self-healing action of the functional glass layer. KCI Citation Count: 8